Role of Frozen Section in Neck Dissection of Oral Cancer Patients - K.M. Hiwale 1 , Arzoo Alagh2 , Sunita Vagha3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Oral carcinoma is emerging as growing problem in many areas of the World and 4th mostcommon cancer among women in India. Globally, over 3,00,000 people are diagnosed with oral cavitycancer each year. Radical or modified radical neck dissection is usually a choice of surgeon in node positivepatients. Frozen section when performed along with supra-omohyoid neck dissection provides solution tothis dilemma of surgeon by detecting the metastasis in cervical lymph nodes intra-operatively during neckdissection. This study was planned to establish usefulness of frozen section examination in decision ofcorrect plan of management of patients of oral cancer with clinically nonodal metastasis in neck (N0).Objectives: To study appropriate plan of management for clinically neck examination with lymph nodestatus N0 in patients of oral cancer and to determine efficacy of frozen section examination in detection ofoccult nodal metastasis in neck in patients of oral cancer.Method and Materials: In 102 cases, excision of lesion, followed by supra-omohyoid neck dissection wasprimary mode of treatment and lymph nodes at various levels were sent to frozen section for assessment ofmetastasis by cancer cells. Intraoperatively during frozen section,if any of the lymphnode between levelsI to levels III is found positive for the metastatic disease then the plan of surgery was changed to a morecomprehensive Modified radical neck dissection.Results: Maximum cases were carcinoma tongue followed by cases of carcinoma of gingiva-buccalsulcus.Carcinomas of stage 1,stage 2,stage 3 are 43.8%, 52.2% and 3.9%. Histopathological grading of oralsquamous cell carcinoma was done by Broader’s grading system as Well differentiated SCC (52 cases),Moderately differentiated SCC (42 cases), poorly differentiated SCC (08 cases). Supra-omohyoid neckdissection was initial plan of management in cases but it changed to modified radical neck dissection in 42cases as lymph nodes between level 1 to 3 were positive for metastasis of SCC.Conclusion: Oral cancer should be surgically managed intra-operatively by frozen section examination ofalllymph nodes to avoid short term recurrences and institution of post-surgicalchemo/radiotherapy. Frozensection examination of yielded lymph nodes in these surgeries canmodify the extent of dissection of neck.